Takayasu Arteritis: The Atypical Presentation of a Rare Disease - Fernandes, Cristiana; Marques, Cristina; Ogando, Ana; Barroso, Ana Sofia; Oliveira, Carlos (Gazeta Médica, 2022)
Takayasu arteritis is a rare, idiopathic, chronic and progressive inflammatory disease that causes narrowing, occlusion and aneurysms of the systemic arteries, mainly affecting the aorta and its branches. Neurological involvement appears in a minority of Takayasu arteritis cases and the occurrence of neurological syndromes as the first manifestation has been rarely reported. For the diagnosis of this vasculitis, the clinical data must be correlated with the findings of the complementary exams, and once the diagnosis is made, prompt therapy should be started in order to minimize organ damage.